2020
DOI: 10.31014/aior.1991.03.03.201
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Government Response to Socioeconomic Impact of Covid-19 Pandemic in Nigeria

Abstract: Since the Nigerian economy is largely dominated by informal workers, the preventive measures (lockdown, movement restriction, social distancing and interstate travel ban) occasioned by Covid-19 pandemic will affect socioeconomic livelihood in Nigeria. Relying on secondary sources, this study examines socioeconomic challenges of Covid-19 pandemic in Nigeria, analyses and evaluates government response to curbing its effect on livelihood in Nigeria. Results from the study find bearings between Covid-19 pandemic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Following an accelerated spread of COVID-19 in Nigeria, the Federal Government ordered an initial 2-week lockdown on March 30th, in 2 states (Lagos and Ogun) as well as the FCT, which was extended by an additional 2 weeks on April 13th. With a teeming population of over 200 million people, 50% of which were living below the international poverty line of US$ 1.25/d [ 14 ], the informal economy represents a crucial lifeline for the increasing number of people unable to secure white collar jobs in Nigeria. The National Bureau of Statistics (NBS) reported that the informal sector was responsible for 80% of job creation in 2019 and contributed 58% to the nation’s Gross Domestic Product (GDP) [ 14 ].…”
Section: On Socio-economic Impact and Palliative Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Following an accelerated spread of COVID-19 in Nigeria, the Federal Government ordered an initial 2-week lockdown on March 30th, in 2 states (Lagos and Ogun) as well as the FCT, which was extended by an additional 2 weeks on April 13th. With a teeming population of over 200 million people, 50% of which were living below the international poverty line of US$ 1.25/d [ 14 ], the informal economy represents a crucial lifeline for the increasing number of people unable to secure white collar jobs in Nigeria. The National Bureau of Statistics (NBS) reported that the informal sector was responsible for 80% of job creation in 2019 and contributed 58% to the nation’s Gross Domestic Product (GDP) [ 14 ].…”
Section: On Socio-economic Impact and Palliative Measuresmentioning
confidence: 99%
“…With a teeming population of over 200 million people, 50% of which were living below the international poverty line of US$ 1.25/d [ 14 ], the informal economy represents a crucial lifeline for the increasing number of people unable to secure white collar jobs in Nigeria. The National Bureau of Statistics (NBS) reported that the informal sector was responsible for 80% of job creation in 2019 and contributed 58% to the nation’s Gross Domestic Product (GDP) [ 14 ]. In lieu of this numbers, the preventive measures associated with the imposed lockdown, such as: movement restrictions, interstate travel ban and physical distancing meant that millions of people in the informal sector, relying on daily income for survival, were rendered unemployed and without a source of income [ 14 ].…”
Section: On Socio-economic Impact and Palliative Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The dwindle allocation in recent time and increase in recurrent expenditures because of the outbreak of COVID-19 pandemic has necessitated the need to re-engineered the revenue drives of the local government for future prospect and development, especially, at post pandemic era. Various researchers had conducted research on the impact of COVID -19 on various areas such as informal economy (Khambule, 2020;Nnabuife, Okoli, & Anugwu, 2020); Government response to socioeconomic (Awofeso & Irabor, 2020); Agriculture (Otekunrin, Otekunrin , Fashina, Omotayo, & Akran, 2020;Singh, Sharma, & Sharma, 2020); Stock market indices (Adekoya. & Nti, 2020); Medical tourism (Sharma, Vishray, Ahlawat, Mittal, & Mittal, 2020); Churches and pastoral ministry (Afolaranmi, 2020); Small and medium scale business (Imache, Tian, Tasinda, & Salisu, 2020); Supply chain (Babatunde, 2020) and Aviation (Siyan, Adegoriola, & Agunbiade, 2020) with less emphasis or focus on the impact on local government internally generated revenues and its administration.…”
mentioning
confidence: 99%